Effect of Total Flavonoids of Rhizoma drynariae on Tibial Dyschondroplasia by Regulating BMP-2 and Runx2 Expression in Chickens - Yao, Wangyuan; Zhang, Hui; Jiang, Xiong; Mehmood, Khalid; Iqbal, Mujahid; Li, Aoyun; Zhang, Jialu; Wang, Yaping; Waqas, Muhammad; Shen, Yaoqin; Li, Jiakui (Frontiers in Pharmacology, 2018)
Tibial Dyschondroplasia (TD) is an abnormality of the growth cartilage that occurs in chickens and other rapidly growing avian species. This disease not only cause huge economic losses, but also greatly affects animal welfare. The total flavonoids of Rhizoma drynariae (TFRD) has been used to cure wide variety of diseases including bone fractures and osteoarthritis and osteoporosis. However, less information is available about the using of TFRD against the TD. The aim of this study was to determine the effect of TFRD on TD by regulating BMP-2 and Runx2 in chickens. A total of 200 birds were randomly divided into control, TD, TD recovery and TFRD groups. All the groups were given standard diet with an addition of thiram (50mg/kg) from day 3 to day 7 in TD, TD recovery and TFRD groups in order to induce TD in chickens. After the induction of TD, the birds of TFRD group were fed standard diet with the addition of TFRD at 20mg/kg. Clinical results conveyed that TFRD can improve the growth performance of the TD chickens and recover normal activity and it is more obvious than TD recovery. Gene expressions of BMP-2 and Runx2 were down-regulated during the development of the disease and were up-regulated obviously after TFRD treatment. In conclusion, TFRD not only decreased the mortality rate but also increased the growth performance of TD in chickens. In conclusion, TFRD plays important role in improving the growth performance, adjusting the relevant physiological indicators and regulating BMP-2 and Runx2 in chickens.